0490 Development and Preliminary Evaluation of a Brief Intervention for Post-Deployment Insomnia. (27th May 2020) - Mellman, T; Howell, M
Abstract: Introduction: Sleep disturbances are common among previously deployed Veterans. Cognitive behavioral therapy for insomnia (CBT-I) has shown promise for Veterans but there are limitations and CBT-I may not optimally target the nocturnal vigilance conditioned by threatening environments. We developed and preliminarily evaluated a brief educational/behavioral intervention that combined established behavioral sleep principles with cognitive exercises intended to reduce the impact of vigilant thoughts and behaviors on sleep. Methods: Participants were 40 Veterans recruited from the community and local VAMC who had been deployed to combat zones or hazardous duty areas. The mean age was 40, and the majority were male, African American, and screened positively for PTSD. They were assigned to the study intervention or an educational control that utilized a pamphlet promoting healthy sleep habits. Assignment at a 2:1 ratio was intended to allow for refinement of the study intervention during the early phase of the trial. Initial assessment was followed by a week of sleep diary collection, then two intervention sessions a week apart, followed by a repeat assessment. Participants of the study intervention were assessed again 3-months later. Results: Improvements in sleep efficiency, ratings for feeling rested in the morning, and reduced Insomnia Severity Index scores were seen in the post-treatment week but did not differ between groups. At 3-months, these improvements were sustained in the 14 retained participants of the study intervention, engagement in vigilance reducing exercises remained high, and ratings of how rested one felt in the morning were significantly improved over ratings from the post-treatment week. Conclusion: Brief behavioral intervention for post-deployment insomnia can provide benefits and cognitive exercises to reduce the impact of vigilant thoughts and behaviors warrant further evaluation. Support: Supported by W81XWH-14-1-0066 from the Congressionally Directed Peer-Reviewed Medical Research Program of the Department of Defense